Historical trends in health care-related financial holdings among members of Congress. - Matthew S McCoy (Public Library of Science (PLoS), 2021)
Background Revelations that some members of Congress, including members of key health care committees, hold substantial personal investments in the health care industry have raised concerns about lawmakers' financial conflicts of interest (COI) and their potential impact on health care legislation and oversight. Aims 1) To assess historical trends in both the number of legislators holding health care-related assets and the value and composition of those assets. 2) To compare the financial holdings of members of health care-focused committees and subcommittees to those of other members of the House and Senate. Methods We analyzed 11 years of personal financial disclosures by all members of the House and Senate. For each year, we calculated the percentage of members holding a health care-related asset (overall, by party, and by committee); the total value of all assets and health care-related assets held; the mean and median values of assets held per member; and the share of asset values attributable to 9 health asset categories. Findings During the study period, over a third of all members of Congress held health care-related assets. These assets were often substantial, with a median total value per member of over $43,000. Members of health care-focused committees and subcommittees in the House and Senate did not hold health care-related assets at a higher rate than other members of their respective chambers. Conclusions These findings suggest that lawmakers' health care-related COI warrant the same level of attention that has been paid to the COI of other actors in the health care system.